Antimicrobial resistance profile of Escherichia coli in drinking water from one health perspective in low and middle income countries - Desye, Belay; Woldetsadik Mawugatie, Temeselew; Asmare, Lakew; Tsega, Yawkal; Melak, Dagnachew; Endawkie, Abel; Daba, Chala (Frontiers in Public Health, 2024)
IntroductionAntimicrobial resistance is a major global public health concern, especially in low-resource settings. In low- and middle-income countries, the existing evidence about antimicrobial resistance in drinking water is inconsistence and not comprehensive. Therefore, this study aimed to estimate the pooled prevalence of antimicrobial resistance profiles of Escherichia coli from drinking water in low- and middle-income countries.MethodsThis study was conducted using comprehensive literature searches using various databases such as PubMed, Scientific Direct, HINARI, and Google Scholar. Data extraction was performed using Microsoft Excel and exported to STATA 14/SE software for analysis. We used the Joanna Briggs Institute’s quality appraisal tool to ensure the quality of the included studies. A random effects model was employed to estimate the pooled prevalence. Publication bias was evaluated using funnel plots and Egger’s regression test. Subgroup and sensitivity analysis were also conducted in this study.ResultsThe study found that the pooled prevalence of Escherichia coli isolates in drinking water was 37.94% (95% CI: 26.73–49.13). The prevalence of multidrug resistance was 43.65% (95% CI: 31.15–56.15). Regarding specific antimicrobials, the pooled resistance levels of Escherichia coli were 54.65% (95% CI: 41.35–67.96) against contrimoxazole, followed by 48.64% (95% CI: −3.6–101) against amoxicillin and 48% (95% CI: −18.1–114.2) against cefuroxime.ConclusionThe findings indicated a significant prevalence of antimicrobial resistance of Escherichia coli isolated from drinking water and its multidrug resistance. To address this issue, it recommends focusing on improving basic hygiene and sanitation practices and enhancing water and wastewater treatment systems.Systematic review registrationIdentifier CRD42024533592.